What Are the Factors That Interplay From Normal Pregnancy to Near Miss Maternal Morbidity in a Nigerian Tertiary Health Care Facility? (2014)
Researchers in Nigeria examined the epidemiological charac teristics and factors associated with maternal outcomes using a mixed method approach: a prospective case control study design involving 375 pregnant women who received maternal care from a tertiary facility and in-depth interviews reporting the experience of near-miss survivors. A generalized ordered logit model was used to generate the estimates of partial proportional odds ratios (and 95% confidence intervals) across categories of the outcome variable. Factors strongly associated with maternal morbidity were late refer ral of women, presence of complications at booking antenatal visits, low birth weight, and severe birth asphyxia. The nearmiss women were further characterized, and a low proportion (25%) had organ dysfunction or failure. The challenge of such diagnoses in resource-constrained settings raises questions about the appropri ateness of using organ dysfunction criteria in developing countries.